Conditions and ways of improvement of training methods of cadets in the Academy of Interior Troops of the MIA of Ukraine - Pylypets A.V (Kharkov National Pedagogical University, 2011)
It was estimate the level of methodological preparation of students of younger courses. In experiment took part educational group of 24 students of military school. It was estimate the level of physical and methodological preparation of students. With the help of experiment was ground the program of methodological preparation. It is recommended concrete scheme technology of methodological preparation. Broadening of students' competence was made by the introducing of new theoretical information - terms and ideas about physical education and sport.